Level and pace of the regional development of Bosnia and Herzegovina in the context of integration into the European union - Tulumović, Vanes (Array, 2020)
The main goal of this paper is to assess the level and pace of regional development of Bosnia and Herzegovina on the one hand, and the Euro-Atlantic path of Bosnia and Herzegovina as a potential candidate for EU membership on the other. In the empirical part of the research, the spatial component encompassed the regionalization of Bosnia and Herzegovina. The research also included an analysis of the process of the integration of Bosnia and Herzegovina into the European Union from the aspect of pre-accession assistance to candidate countries and potential candidates in the function of promoting regional development. The primary research of regional development and assessment of the level of development as well as the scope of structural policies in overcoming the key political, social and economic problems that hinder the development and improvement of the economic integration of Bosnia and Herzegovina towards the European Union are limited to the territory of Bosnia and Herzegovina. The basic scientific methods used in the work and for giving answers to research questions are historical and comparative methods. They consist of methods and indicators of statistical analysis (indices, growth rates, participation rates, coefficients, averages). Specific scientific methods used in the process of this work are: the method of analysis, the synthesis method, the induction method, the descriptor method, the deduction method, the classification method and the comparison method. The empirical results of the research confirm that Bosnia and Herzegovina is faced with the problem of regional development with a pronounced imbalance between the areas within the whole territory of Bosnia and Herzegovina. This is a confirmation for the need for systemic policy as well as regional development policy at the level of Bosnia and Herzegovina that would be in line with the policies of the European Union.